Living Alliances, Leaving Alliances - Orban, Franck; Strand Larsen, Elin (2022)
Throughout history, alliances have taken many different forms and they have been difficult to understand in their totality. As we now experience an unprecedented pandemic, which highlights the need for both external alliances between states and internal alliances between governments and populations, understanding alliances is more than ever critical to apprehend an open and interactive world that knows no borders and in which challenges imposed on humans are global. The book “Living Alliances, Leaving Alliances” is an interdisciplinary approach to investigating past, present and future alliances on an interpersonal, subnational, international and transnational level. It is the result of a two-year project by AreaS, a research group in area studies located at the Østfold University College in Norway.